FAKTOR-FAKTOR YANG MENYEBABKAN KURANGNYA MOTIVASI ORANG TUA UNTUK MELANJUTKAN PENDIDIKAN ANAK KE TINGKAT SMP DI KAMPUNG SUNGAI SALAK NAGARI KOTO RAWANG KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN - HARTATI, KORI - (Pendidikan Sosiologi, 2014)
From the data found in Sub-District Sungai Salak District Koto IV Jurai RawangDistrict of South IV Jurai Coastal District Pesisir Selatan of the Year 2010 - 2013 there aremany children who do not continue their education at junior high school and the lack ofmotivation of parents to continue their education. This study aimed to describe the factors thatcause a lack of motivation of parents to continue their education to junior level in Sub-DistrictSungai Salak District Koto Rawang District of South IV Jurai Coastal District Pesisir Selatan.This study used a qualitative research approach with descriptive type. Methods of data collectionis done in three ways: (1) observation, (2) Interview, (3) study the document. The unit of analysisis the individual. Analysis of the data used by the interactive model of data analysis modelsMilles and Huberman. The results of this study indicate that the factors that cause a lack ofmotivation of parents to continue their education to junior level in Sub-District Sungai SalakDistrict Koto Rawang District of South IV Jurai Coastal District Pesisir Selatan, namely: 1.Intrinsic motivation of parents do not continue to junior high school level childrenseducation (a) the perception of parents who think that education is not going to change lives. (b)family economic situation is inadequate. 2. Motivation Extrinsic parents do not continue theireducation for junior high kids to (a) social custom to marry off their children at a young age.